2019
DOI: 10.1186/s13287-019-1225-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulating autophagy in mesenchymal stem cells effectively protects against hypoxia- or ischemia-induced injury

Abstract: In mammals, a basal level of autophagy, a self-eating cellular process, degrades cytosolic proteins and subcellular organelles in lysosomes to provide energy, recycles the cytoplasmic components, and regenerates cellular building blocks; thus, autophagy maintains cellular and tissue homeostasis in all eukaryotic cells. In general, adaptive autophagy increases when cells confront stressful conditions to improve the survival rate of the cells, while destructive autophagy is activated when the cellular stress is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 119 publications
3
38
0
5
Order By: Relevance
“…Identifying the mechanism that regulates the responses of MSCs to external stimuli has important implications in designing optimal expansion and delivery strategies for MSC therapeutic applications (Galipeau & Sensebe, 2018;Yin et al, 2019). MSCs are highly responsive to microenvironmental stimuli arising from biological parameters, for example, immunomodulatory cytokines (Gao et al, 2016;Zhao, Ren, & Han, 2016), biomechanical regulation, for example, culture surface tension or stiffness (Bijonowski et al, 2019;Cesarz, Funnell, Guan, & Tamama, 2016), and physiological modulation, for example, oxygen tension (Hu, Zhao, Wu, & Li, 2019;Peck et al, 2019). Our previous studies have indicated that the significant alterations of MSC aggregates are due to different levels of cortical compaction-induced metabolic reconfiguration rather than hypoxic core within aggregates (Bijonowski et al, 2019;Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the mechanism that regulates the responses of MSCs to external stimuli has important implications in designing optimal expansion and delivery strategies for MSC therapeutic applications (Galipeau & Sensebe, 2018;Yin et al, 2019). MSCs are highly responsive to microenvironmental stimuli arising from biological parameters, for example, immunomodulatory cytokines (Gao et al, 2016;Zhao, Ren, & Han, 2016), biomechanical regulation, for example, culture surface tension or stiffness (Bijonowski et al, 2019;Cesarz, Funnell, Guan, & Tamama, 2016), and physiological modulation, for example, oxygen tension (Hu, Zhao, Wu, & Li, 2019;Peck et al, 2019). Our previous studies have indicated that the significant alterations of MSC aggregates are due to different levels of cortical compaction-induced metabolic reconfiguration rather than hypoxic core within aggregates (Bijonowski et al, 2019;Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MSCs cultured under hypoxic condition could improve their regenerative potential in variety of tissues [31,32]. Improved potential of the hypoxia-preconditioned MSCs has been reported for different clinical applications including spinal cord and lung injury, hindlimb ischemia and immune-de cient models due to improving their secretion of reparative factors [33,34], and initiating autophagy [35]. Thus, in this study, to further develop the isolation and culture method without using the MDPSC isolation device for DPSC subsets with high regenerative potential, DPSCs were cultured under stable hypoxic (5%) and pH condition which were con rmed by non-contact oxygen analyzer and pH meter.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic condition signi cantly reduces apoptosis of MSCs in vitro [49]. Enhanced survival and retention of hypoxic preconditioned MSCs are reported after injection in a spinal cord injury [50], muscle [51], and a cerebral infarction [35]. The role of HIF-1α in cell viability and anti-apoptosis of MSCs has been suggested [52].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS also cause severe oxidative stress, which can promote DNA damage, endothelial dysfunction and local inflammatory responses. On the basis of ischemia, reperfusion triggers the release of intracellular and extracellular damage-associated molecular pattern molecules (DAMPs), therefore, resulting in the accumulation of inflammatory cells such as monocytes, dendritic cells and so on [5].…”
Section: Introductionmentioning
confidence: 99%